Find the just common denominator \( \frac{4}{6} \) + \( \frac{2}{3} \)

\( \frac{4}{6} \) + \( \frac{2}{3} \)
First, simplify \( \frac{4}{6} \) to \( \frac{2}{3} \) / Your problem should look like: \( \frac{2}{3} \) + \( \frac{2}{3} \)
Second, join the denominators. / Your problem should look like: \( \frac{2+2}{3} \)
Third, simplify. / Your problem should look like: \( \frac{4}{3} \)
Fourth, convert to mixed fraction. / Your problem should look like: \( 1\frac{1}{3} \)

Mixed number form: \( 1\frac{1}{3} \)
Exact form: \( \frac{4}{3} \)

\( \frac{4}{6} + \frac{2}{3} \) =?

You need to find a common denominator to add them which is 6

6×1=6 and 3×2=6

What you do on the denominator, you must do in the numerator

\( \frac{4}{6} + \frac{4}{5} \) = \( \frac{8}{6} \)

To reduce, find a common factor which in this case is 2

8÷2=4 and 6÷2=3 ⇒ \( \frac{4}{3} \)

To change to a mix fraction, divide the numerator by the denominator

\( \frac{4}{3} \) ⇒ \( 1 \frac{1}{3} \) 
Answer: \( \frac{4}{3} \) as an improper fraction or \( 1 \frac{1}{3} \) as a mixed fraction 


RELATED: